Examine the Effectiveness of Marketing Communication via Facebook in Malaysia - Cheah, Peter Song Boo (2010)
Since its launch in 2004, Facebook has grown so big that it has become part of our life. It is one of the fastest growing and most popular among the social networks. Facebook has a larger population than most countries (Levy, 2010). A recent research by Nuttney (2010) on the social networking market opportunity indicates that among all Social Network Sites (SNSs), Facebook is the world’s largest social network and it is the only truly global network. Therefore, Facebook offers marketers an unparalleled opportunity to connect with fans and consumers. There are arguments on the ability of using Facebook or other SNSs to sell advertisements. Users get on to Facebook to socialize with their friends and not hunt for products. However, the question now is not “how advertising will work on Facebook” but rather “how Facebook and other SNSs are changing advertising”. Levy (2010) states that Facebook has become popular with not only individuals, but companies as well because it provides a suite of features that allow companies to develop communities, humanize their brands, interacts with their prospects and customers, and many other benefits With the limited space and restrictive guidelines on Facebook Ad as highlighted by Levy (Levy 2010), the problem is how to make your ad stand out from the clutter is the key issue. With all the spamming, online scams, privacy issues and complaints about Fan Pages simply tag users, therefore, is the current Facebook platform ready for advertisers to use as a marketing communication tool? Hence, this study is undertaken with the aim of finding out the effectiveness of marketing communication via Facebook. The framework adopted in this study is based on a simple and commonly used model – AIDA (attention, interest, desire and action). This model is one of the hierarchy of effects models. The model suggests that before an actual purchase takes place, the target consumer has to be aware of the brand or product. Awareness will generate interest that will subsequently lead to desire to purchase the brand or product (Saxena, 2006). A questionnaire was developed to which a total of 266 respondents within Malaysia participated. The data collected from the survey were analyzed using a statistical software application named SPSS version 19. SPSS was used to measure the reliability, means, bivariate correlation and crosstabulation analysis. Three interviews were also conducted with a Brand Manager from Johnnie Walker Malaysia, a small business specializing in lady accessories called Dep Accessories and the Digital Director of Omnicom Media Group, a media services specialist in Malaysia, The empirical study shows some positive results however they are not super fantastic as the hype of many literature reviews. Facebook Ad is good for brand visibility however users rarely click on it; Fan Page is useful provided that it is targeting the right consumers and giving the right message. However, Facebook is a very powerful tool for word-of-mouth and viral marketing. In conclusion, marketing communication via Facebook is suitable for certain brands and need to be managed carefully. It cannot be a “standalone” marketing communication tool but it is a very good supporting tool for integrated marketing communication (IMC) mix. Marketers are encouraged to fully capitalize on Facebook’s functions and features in order to enhance the impact of their IMC campaign. A discussion on the implications was put forth and recommendations were given in this study.